“PERAN PROBIOTIK LACTOBACILLUS DALAM PRODUKSI TERNAK BERKELANJUTAN: TINJAUAN SISTEMATIS TERHADAP EFIKASI BIOLOGIS DAN PENINGKATAN PERFORMA” - Riyanto; Kharisma Putriani; Septian Nur Fauzy; Ayu Cahya Risquna; Setya Budhi Udrayana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Antibiotic use in livestock production contributes significantly to antimicrobial resistance, creating urgency for more sustainable alternatives. Lactobacillus-based probiotics have been widely explored, but their effectiveness varies depending on livestock species, strain, dosage, and rearing conditions, highlighting the need for comprehensive evaluation. This systematic review aimed to assess the role of Lactobacillus in suppressing pathogenic bacteria, improving animal performance, and its potential as an alternative to antibiotics or antibiotic growth promoters (AGPs). The study applied a Systematic Literature Review approach using the PICO framework and PRISMA guidelines. Literature searches were conducted in Scopus, Web of Science, PubMed, and ScienceDirect, focusing on empirical studies published in the last 10 years. Study quality was assessed using MMAT, and data were synthesized through thematic analysis with NVivo 14. Out of 106 identified records, 61 studies met the inclusion criteria. The findings indicate that Lactobacillus suppresses pathogens through competitive exclusion, acidification of the gut environment, and production of antimicrobial metabolites. Evidence of improved performance was strongest in broilers and pigs, particularly in weight gain and feed efficiency, while layers showed improvements in egg production. However, variability across studies suggests context-dependent outcomes. Overall, Lactobacillus shows strong potential to reduce antibiotic reliance, though further research is needed to standardize applications and validate its effectiveness across production systems.